Influência do uso e ocupação do solo sobre a qualidade e quantidade de água superficial em três microbacias - Bertão, Norma Cristina (2015)
This study was to evaluate the anthropogenic interference arising from the use and occupation of land on the flow and water quality three watersheds (Cerrado, Pasture, Agricultural) in the municipality of Campo Verde - MT. Collected were taken water samples from December / 2012 to June / 2013. During the rainy season, the samples were taken every two weeks and the dry period every month. In between manual collection, sample collection were performed with autosampler Bulher 2000 with two activation programs, with the first set to collect at set intervals and the second to collect water every five minutes to detail the variation of nutrients during precipitation. Monitoring the flow was done with digital acoustic reel OTT ADC. The turbidity, temperature, dissolved oxygen and the variation of the water column were measured by automated Hydrolab DS5X probe. The analysis of anions (fluoride, chloride, nitrate and sulfate) were analyzed in the chromatograph Metrohm Compact IC 761, the cations (potassium, sodium, calcium, aluminum, magnesium and silicon) were analyzed in the Perkin Elmer Optima 4300 ICP-ES Dv and dissolved organic carbon analysis was performed in Spectrolyser OTT. The nutrients in every period were not considered statistically different. Flow rates were significant differences in the dry season, the turbidity in the Cerrado watershed in the absence of surface runoff obtained variations near 0 NTU. There was a significant increase in turbidity and flow monitoring in the rainy season. In the agricultural area was found higher turbidity in the water. The parameters analyzed did not exceed the limits established by CONAMA Resolution 357/2005 indicating good preservation in the waters of watersheds due to the presence of areas of permanent preservation.